Molokhia leaf extract prevents gut inflammation and obesity. (15th July 2020) - Lee, Hye-Bin; Oh, Mi-Jin; Do, Moon Ho; Kim, Young-Soo; Park, Ho-Young
Abstract: Ethnopharmacological relevance: Molokhia is highly consumed in Egypt as edible and medicinal plants, and its leaves are used for the treatment of pain, fever, and inflammation. Aim of the study: High-fat diet (HFD) induces gut dysbiosis, which is closely linked to metabolic diseases including obesity and leaky gut. The effects of molokhia ( Corchorus olitorius L.) on anti-obesity and gut health were investigated in this study. Materials and methods: The effects of a water-soluble extract from molokhia leaves (WM) on lipid accumulation in 3T3-L1 adipocytes and on body weight, gut permeability, hormone levels, fecal enzyme activity of the intestinal microflora, and gut microbiota in HFD-induced C57BL/6J mice were examined. Results: WM treatment significantly inhibited lipid accumulation in 3T3-L1 adipocytes. Mice treated with 100 mg/kg WM had 13.1, 52.4, and 17.4% significantly lower body weights, gut permeability, and hepatic lipid accumulation than those in the HFD group, respectively. In addition, WM influenced gut health by inhibiting metabolic endotoxemia and colonic inflammation. It also altered the composition of the gut microbiota; in particular, it increased the abundance of Lactobacillus and decreased that of Desulfovibrio . Conclusion: Our results extend our understanding of the beneficial effects of WM consumption, including the prevention of gut dysbiosis and obesity. Graphical abstract: Image 1 Highlights: MM ameliorated the high-fat diet-induced obesity and gut dysbiosis. WM decreased body weight gain, hormone levels, and hepatic lipid accumulation. Prevention of the leaky gut leads to inhibit metabolic endotoxemia and colonic inflammation. WM regulated the gut microbiota through increasing the abundance of Lactobacillus.